X—two shoes and a fountain: ecstasis, mimesis and engrossment in Heidegger’s The Origin of the Work of Art - Mulhall, S (Oxford University Press, 2019)
In this essay, I argue for three interpretative claims about the philosophical strategies and examples employed in the first of Heidegger’s three lectures on ‘The Origin of the Work of Art’. I argue that his initial response to a Van Gogh painting is intended to dramatize a confusion rather than to articulate an insight; that his invocation of a poem by C. F. Meyer serves a number of functions overlooked by other commentators; and that Heidegger’s overall approach is best understood in terms of Michael Fried’s conception of modernism in painting.